2021
DOI: 10.3389/fphar.2021.696065
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Rifaximin Versus Placebo or Other Active Drugs in Critical ill Patients With Hepatic Encephalopathy

Abstract: Objective: Rifaximin has been approved for use as a first-line therapy for secondary prophylaxis of hepatic encephalopathy (HE). This article is to update existing evidence on efficacy and safety of rifaximin treatment and prevention for HE.Methods: We systematically searched multiple databases until January 31 2021. The studies compared rifaximin vs. placebo or other active drugs (i.e., nonabsorbable disaccharides, other antibiotics, L-ornithine-L-aspartate (LOLA), and probiotics) for patients with overt HE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…It is unclear whether RFX directly improves survival in patients with HE, with conflicting results reported in two independent meta-analyses when compared with active treatments or placebo 14 23. Other studies have suggested that RFX treatment may improve survival, but this remains to be substantiated by larger RCTs 24–27…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is unclear whether RFX directly improves survival in patients with HE, with conflicting results reported in two independent meta-analyses when compared with active treatments or placebo 14 23. Other studies have suggested that RFX treatment may improve survival, but this remains to be substantiated by larger RCTs 24–27…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of RFX was evaluated in a meta-analysis of 28 randomised controlled trials (RCTs) of RFX versus other active drugs or placebo for patients with HE. In that analysis, RFX was shown to significantly reduce HE grade, improve cognitive impairment and reduce recurrent episodes but no significant improvement in mortality was observed 14. Follow-up lengths for the included RCTs ranged from 3 days to 6 months, leaving the long-term effect of RFX treatment on survival unclear 14…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…значительно уменьшило когнитивные нарушения у пациентов с MПЭ. Помимо этого, в ходе анализа подгрупп было доказано, что рифаксимин-α превосходит плацебо в достижении регресса МПЭ [47].…”
Section: лечение мпэunclassified